1991
DOI: 10.1021/bi00108a006
|View full text |Cite
|
Sign up to set email alerts
|

Human substance P receptor (NK-1): organization of the gene, chromosome localization and functional expression of cDNA clones

Abstract: The gene for the human substance P receptor (NK-1) was cloned using cDNA probes made by the polymerase chain reaction from primers based on the rat sequence. The gene spans 45-60 kb and is contained in five exons, with introns interrupting at sites homologous to those in the NK-2 receptor gene. Analysis of restriction digests of genomic DNA from mouse/human cell hybrids indicates the NK-1 receptor is a single-copy gene located on human chromosome 2. Polymerase chain reaction using primers based on the 5' and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
105
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(109 citation statements)
references
References 38 publications
4
105
0
Order By: Relevance
“…In its full-length form, NK1R is a protein of 417 amino acids (80). It belongs to the class I of GPCRs and can be coupled to several groups of G proteins: the Gαq, Gαs and the Gαi (81,82).…”
Section: The Substance P/neurokinin-1 Receptormentioning
confidence: 99%
“…In its full-length form, NK1R is a protein of 417 amino acids (80). It belongs to the class I of GPCRs and can be coupled to several groups of G proteins: the Gαq, Gαs and the Gαi (81,82).…”
Section: The Substance P/neurokinin-1 Receptormentioning
confidence: 99%
“…It has been shown that limbic binding sites for SP are colocalized with those of monoamine neurotransmitters (Dietl and Palacios, 1991;Elliot et al, 1986;Gerard et al, 1991;Hershey and Krause, 1990;Hökfelt, 1991;Hopkins et al, 1991;Masu et al, 1987;Takeda and Krause, 1991;Yokota et al, 1989). SP displays highest affinity for tachykinin, type 1 [NK 1 ] receptors (Otsuka and Yoshioka, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The human NK1R gene (2)(3)(4)(5), localized to chromosome 2, has been cloned. NK1R is a member of the G protein-coupled receptor (GPCR) superfamily and has a structure of seven transmembrane domains, an extracellular amino terminus and an intracellular carboxyl terminus (2).…”
mentioning
confidence: 99%